The Gluten-free diet and oncological prevention – the importance of a conscious lifestyle for physically active people – A Literature Review - Wątor, Julia; Podolska, Alicja; Kolano, Patrycja; Krzeszowiak , Jerzy; Chojnacka , Barbara; Pulanecki , Tomasz; Boba , Barbara; Bryksy , Sylwia; Ożga , Aleksandra; Woźniacka , Agnieszka (Quality in Sport, 2025)
Introduction: Celiac disease is a chronic autoimmune disorder triggered by gluten ingestion in genetically predisposed individuals. If untreated, it leads to villous atrophy, chronic inflammation, and immune dysfunction. Studies show that active, untreated celiac disease increases cancer risk, particularly for lymphomas and gastrointestinal malignancies. The only effective treatment is a gluten-free diet. Recent research also suggests that regular physical activity may help modulate inflammation and boost immunity, potentially lowering cancer risk in autoimmune conditions like celiac disease. Aim of the Study: This review examines whether celiac patients are more prone to cancer and how a gluten-free diet modifies this risk. It focuses on cancers commonly linked to celiac disease—lymphomas, small intestine, esophageal, and hormone-related cancers—based on epidemiological, clinical, and pathophysiological studies. Materials and Methods: This review analyzes recent scientific literature, including cohort studies and meta-analyses, on the link between celiac disease and cancer. Increased risks are most evident for enteropathy-associated T-cell lymphoma, small intestine adenocarcinoma, and esophageal squamous cell carcinoma. Risk factors include chronic mucosal inflammation and immune dysregulation, especially before diagnosis or in those not adhering to dietary guidelines. Conclusions: A gluten-free diet is crucial for symptom control and cancer prevention, promoting mucosal healing and immune normalization. Long-term adherence significantly lowers cancer risk, often to general population levels. While data on stomach and colon cancer remain mixed, no elevated risk is seen in compliant patients. Interestingly, hormone-related cancers (e.g., breast, ovarian) may be less common, possibly due to altered hormone levels. Importantly, regular physical activity offers added protection by reducing inflammation and improving immune function.